The Effect of Room Temperature on the Spread of the Covid-19 Virus by Creating a Special Isolation Room with a Hot Temperature for Those Indicated as Medical Service Facilities - Anwar, Hendi (Bina Nusantara University, 2022)
During the Covid-19 pandemic, there were many alternatives to anticipate or anticipate through certain tools and media with less effectiveness and endanger the users, for example, a device that can be called a disinfecting chamber or